The Implementation of Traders’ Healthy Behavior in the Traditional Market of Kupang City - Yolenta Mariani; Petrus Romeo; Enjelita M Ndoen (Lontar : Journal of Community Health, 2021)
The healthy behavior of traders is essential to prevent the risk of disease transmission in the traditional market. However, most traders do not have the awareness to behave healthily during their activities in the market. This study aimed to portray the implementation of healthy behavior among Oeba Market traders. The portrayal consisted of mosquito larvae eradicating behavior, smoking behavior, and the behavior of using clean water. This research utilized a qualitative approach with six informants who are permanent traders in the Oeba traditional market. Data collection employed observations and in-depth interviews. The results showed that informants had only applied clean water using behavior. Barriers such as inadequate facilities and lack of health information and stakeholders’ supports have contributed to the unwillingness and inability to apply non-smoking and mosquito larvae eradicating behavior in the traditional market. Effective communication and supporting facilities provision could be the key to encourage healthy behavior by market traders.